Cadmium (Cd) heavy metal reduction in liquid and soil using indigenous soil bacteria isolated from Cd-contaminated paddy fields - Hadi, Sapto Nugroho; Haryanto, Totok Agung Dwi; Tamad, Tamad; Ahadiyat, Yugi R. (Brawijaya University, 2025)
The challenge in Indonesian agriculture is the contamination of cadmium (Cd) in rice fields. Cadmium contamination in rice fields is a serious environmental and health problem. Reducing Cd contamination from rice fields is essential. One way is through the use of indigenous microbes. The study aimed to obtain indigenous bacteria from Cd-contaminated rice fields and determine their ability to reduce Cd contamination in liquid and soil media. Soil samples were taken from six locations of Cd-contaminated rice fields in Banyumas Regency, Central Java, Indonesia. The population of soil bacteria was calculated. Selected isolates were tested for their tolerance and ability to reduce Cd. Potential isolates were identified based on their 16S rDNA sequences. The results showed that the most prominent Cd-tolerant bacteria were found in soil samples from Ajibarang, with 1.8 × 106 CFU/g of soil. The study obtained five isolates with high tolerance to Cd, up to 100 ppm, and was able to reduce Cd by 45.58% to 70.02% in liquid media and from 0.92 ppm to 0.02 ppm in soil media. All bacterial isolates are non-pathogenic to plants. Isolate GML2, SRU2, and KBS1 were from Priestia megaterium, JTL1 was from Neobacillus ginsengisoli, and PLK1 was from Gottfriedia sp. The isolates have the potential to be used to reduce Cd contamination and remediate rice fields contaminated with Cd.